Empreendedor 50+: barreiras e estratégias de enfrentamento para empreender - Shinohara, Eloisa Elena Ramos Dias (2022)
The world population is aging rapidly and progressively, because of the global demographic transition process that began in the mid-20th century. According to the World Health Organization (WHO) Europe is the fastest aging continent in the world and in 2016, Brazil had the fifth oldest population in the world. Individuals in the age group of 50 years are people with experience, expertise, and resilience that the time lived has provided and allowed them to embrace new opportunities. This whole scenario motivated the elaboration of this thesis, which aims to identify how the 50+ entrepreneur faces the barriers to undertake and what are the coping strategies experienced. To meet this objective, this thesis was prepared through an alternative structure of three sequential and complementary studies. Study 1 aimed to understand, through the Systematic Literature Review (RSL), the main approaches and themes of studies that investigate 50+ entrepreneurship. The results suggest that this is an emerging and growing theme, highlighting important social impacts, opportunities for studies still little explored in the literature and refractory institutional and cultural considerations. This review grouped the body of knowledge on 50+ entrepreneurship into five thematic groups, such as human, social, senior identity, market, and normative conjuncture, which highlighted gaps and new insights suggesting the expansion of this theme. Thus, study 2, based on the gaps found in the RSL conducted, aimed to identify how entrepreneurs 50+ deal with barriers and strategies to overcome them in the process of creating and running their businesses, from the perspective of experts. A qualitative, descriptive, and exploratory research was conducted, and data collection took place through a focus group and semi-structured interviews with thirteen specialists who work in the area. The results were grouped into three categories: motivations, barriers and coping strategies, revealing that financial motivations and flexibility more often drive the 50+ to undertake; social exclusion, ageism and lack of support were identified as the main barriers and; the search for mentoring and professional counseling as the main coping strategy. The results of the RSL and the perception of experts drove the third study, which aimed to analyze, from the perspective of entrepreneurs 50+, the barriers and coping strategies they experience. This is a qualitative, exploratory, and descriptive research and had the participation of 32 entrepreneurs 50+, with already consolidated ventures and others in the consolidation phase, interviewed online. The results show that the main barriers were the inability with personal marketing, dealing with technology and technological advances, but the non-identification with social media. Among the coping strategies, the ones that drew the most attention were the option to seek learning in courses and readings, in addition to professional help with career mentors or coaching. As a contribution, this thesis demonstrates the need to expand access to education and training, through an entrepreneurship program tailored to the 50+ and to encourage learning in modern technologies, as a resource to increase the participation rates of these entrepreneurs in the labor market. It also brings the need to promote public policies in support of this growing population, especially in Brazil.